Etching characteristics of SiC, SiO2, and Si in CF4/CH2F2/N2/Ar inductively coupled plasma: Effect of CF4/CH2F2 mixing ratio. (14th September 2016) - Lee, Jongchan; Efremov, Alexander; Kim, Kwangsoo; Kwon, Kwang-Ho
Abstract: This study investigated the etching characteristics and mechanisms of SiC, Si, and SiO2 in CF4 /CH2 F2 /N2 /Ar inductively-coupled plasmas. The investigation showed that a change in the CF4 /CH2 F2 mixing ratio at fixed N2 and Ar fractions in a feed gas causes a decrease in the etching rates of SiC and Si, but results in an almost constant SiO2 etching rate. Plasma chemistry was analyzed using Langmuir probe diagnostics and optical emission spectroscopy. The good agreement between the behaviors of both the SiC and the Si etching rates with a change in F atom density suggested a neutral-flux-limited etching regime for these materials. On the contrary, the SiO2 etching process appeared in the transitional regime of the ion-assisted chemical reaction and was influenced by both neutral and ion fluxes.